Firm reputation and employee startups - Jan Zabojnik (Queen's University, Department of Economics, 2016)
This paper studies a repeated-game model in which firms can build a reputation for rewarding innovative employees. In any Pareto efficient equilibrium, low-value innovations get developed in established firms, while high-value innovations get developed in startups. The threshold level can be discontinuous, so otherwise similar firms may exhibit very different levels of innovation. The paper also shows that the optimal incentive contract for innovative employees has an option-like form, and that a firm may want to worsen the distribution of possible innovations. The model's predictions are consistent with a broad set of observed regularities regarding the creation of employee startups.
Keywords: L14; L26; O31; O34; M13; 330; Startups; innovation; reputation; venture capital markets